TAX POLICY IN SERBIAN AGRICULTURE - Simonović, Zoran; Jeločnik, Marko; Subić, Jonel (Economics of Agriculture, 2013)
In paper was analysed tax policy in agriculture of Serbia. Tax policy was observed through the current legal framework, as like: Individual Income Tax Law and Corporate Profit Tax Law. Special attention was paid to the Value Added Tax Law, primarily from the aspect of family agricultural husbandries, as from the stand point of the rules that were valid under the old VAT Law, as well as based on last amendments and supplements adopted at the end of 2012. Mentioned approach of VAT studying is leaned on fact that it represents modern form of tax applicable in field of consumption. It was implemented primarily to facilitate the reduction of the grey economy, to harmonize national tax policy with European Union (EU) standards, as well as to increase tax collection.